Beauty and aesthetic appeal of sports: aesthetic training of athletes - Medvedev, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the aesthetic education standards in student community and their need for basic aesthetic education in the physical education curriculum. Methods and structure of the study. We sampled for the questionnaire survey the 4-year students (n=120) from the Yekaterinburg Institute of Physical Culture’s Humanitarian and Socio-Economic Departments majoring in Physical Education discipline. Results and conclusion. Having analyzed the questionnaire survey data in the context of the ongoing aestheticization of the professional sports, we would make the following preliminary conclusions. First it should be emphasized that the physical education faculties and students recognize the need for modern aesthetic education in the professional training systems, with such education being particularly beneficial for the sports managing community. Second, there is a clear need for a broad discussion of a basic aesthetic education curriculum for the physical education universities – that should cover the whole academic study period on an uninterrupted basis. And third, there is a growing need for the modern aesthetic education and training methods and models as complementary to the traditional academic physical education curriculum. The traditional studies and lectures, no matter how important they are, are not always sensitive to the ever-changing demands of the student community, and should give way to a range of modern interactive training tools. These transformations deserve special attention and support from the academic educational system management. It should be also emphasized that modern education should not prioritize the notorious competences as such anymore, since every trainee’s individuality should be respected and personality progress facilitated by a variety of education tools including modern aesthetic education and training ones – that expand the professional limitations and facilitate individual progresses by improvements in harmony and synergy of the physical and spiritual growth process.